COVID-19 vaccinology landscape in Africa - Baptista, Sara; Naidoo, Sanushka; Suliman, Sara; Nepolo, Emmanuel; Kanoi, Bernard N.; Gitaka, Jesse; Blessing, Oyedemi Mbaebie; Enany, Shymaa (Frontiers in Immunology, 2022)
More than two years after the start of COVID-19 pandemic, Africa still lags behind in terms vaccine distribution. This highlights the predicament of Africa in terms of vaccine development, deployment, and sustainability, not only for COVID-19, but for other major infectious diseases that plague the continent. This opinion discusses the challenges Africa faces in its race to vaccinate its people, and offers recommendations on the way forward. Specifically, to get out of the ongoing vaccine shortage trap, Africa needs to diversify investment not only to COVID-19 but also other diseases that burden the population. The continent needs to increase its capacity to acquire vaccines more equitably, improve access to technologies to enable local manufacture of vaccines, increase awareness on vaccines both in rural and urban areas to significantly reduce disease incidence of COVID-19 and as well as other prevalent diseases on the African continent such as HIV and TB. Such efforts will go a long way to reduce the disease burden in Africa.